A New Fractal Printed Dipole Antenna Based on Tent Transformations for Wireless Communication Applications - Ali, Jawad K. (Al-Khwarizmi Engineering Journal, 2019)
In this paper, a compact multiband printed dipole antenna is presented as a candidate for use in wireless communication applications. The proposed fractal antenna design is based on the second level tent transformation. The space-filling property of this fractal geometry permits producing longer lengths in a more compact size. Theoretical performance of this antenna has been calculated using the commercially available software IE3D from Zeland Software Inc. This electromagnetic simulator is based on the method of moments (MoM). The proposed dipole antenna has been found to possess a considerable size reduction compared with the conventional printed or wire dipole antenna designed at the same design frequency and using the same substrate specifications. Results have shown that the proposed design possesses a multi-band resonant behavior with adequate radiation performance with VSWR ≤ 2 (return loss ≤-10 dB) throughout the resonating bands. This makes the presented antenna (or its monopole counterpart) suitable for use in the modern multi-functions compact communication systems.